Caribbean Report 10-07-1995 - Richards, Ken (anchor); Fraser, Tony (correspondent); Seepaul, Occah (interviewee); Sobion, Keith (interviewee); Weatherill, Bernard (interviewee); Hudson-Phillips, Karl (interviewee); d'Auvergne, Ausbert (interviewee); Draper, Gordon (interviewee); Panday, Basdeo (interviewee) (The British Broadcasting Corporation, 1995)
In this report: the Speaker of Trinidad and Tobago's House of Representatives, Ms. Occah Seepaul, refuses to stand down in a no confidence debate brought against her by the government. Meanwhile, the Attorney General Keith Sobion states that the government will take the matter to the full distance. Lord Weatherill, Former Speaker of the British House of Commons comments that this matter should not be taken lightly by Madame Speaker. In St. Lucia, the commission of inquiry into the alleged misuse of UN funds has resumed without key witness Dr. Charles Flemming. The Commission heard from former Permanent Secretary in the Ministry of Planning, Ausbert d'Auvergne. Trinidad and Tobago's Opposition Leader Basdeo Panday has denied that his United National Congress (UNC) is standing in the way of a Caribbean court of appeal. Following the end of the CARICOM Summit, Caribbean Report asked members of the press corps if it was all plain sailing in terms of the coverage of the Summit.
1. Headlines with Ken Richards (00:00-00:34)
2. Trinidad's Speaker of the House of Representatives refuses to give up her seat in a motion of no confidence debate (00:35-06:55)
3. St. Lucia resumes its commission of inquiry into the UN funds scandal but a key witness fails to show up (06:56-09:56)
4. Trinidad's Opposition is accused of blocking the way forward for a regional court of appeal (09:57-12:00)
Keywords: Parliamentary practice -- Trinidad and Tobago; Legislative bodies -- Trinidad and Tobago -- Presiding officers; Trinidad and Tobago -- Politics and government; Constitutional law -- Great Britain; Great Britain -- Politics and government; Governmental investigations -- Saint Lucia; Political corruption -- Saint Lucia; Saint Lucia -- Politics and government; Appellate courts -- Trinidad and Tobago; Courts of last resort -- Caribbean Area; Journalists -- Caribbean Area; Reporters and reporting -- Caribbean Area; Trinidad and Tobago. Parliament; Caribbean Court of Justice